Users' perceptions and preferences towards maxillary removable orthodontic retainers: a crossover randomized clinical trial - Diego Coelho LORENZONI; José Fernando Castanha HENRIQUES; Letícia Korb da SILVA; Arthur César de Medeiros ALVES; Giédre BERRETIN-FELIX; Guilherme JANSON
Abstract The aim of this study was to assess, correlate, and compare users' perceptions and preference related to maxillary removable retainers. Volunteers were recruited to use four retainer types: conventional wrap-around (CWA), wrap-around with an anterior opening (OWA), "U" wrap-around (UWA), and clear thermoplastic retainer (CT). The main outcomes were the volunteers' perceptions, evaluated with a 100-mm visual analogue scale, and their preferred retainer. The retainers were used for 21 days each (washout intervals of 7 days). Nineteen volunteers (27 ± 4.53 years) were randomly divided into four groups that used the four retainers, but with a different sequence. Perceptions were evaluated immediately after the use of each retainer and the preference at the end of the research. Repeated measures ANOVA and Friedman tests with post-hoc Tukey's test (intergroup comparisons), and Pearson and Spearman analyses (correlations between perceptions) were applied. The WA retainers did not significantly differ among themselves. The CT was rated significantly worse in speech (p ≤ 0.001), discomfort (p < 0.001), and occlusal interference (p < 0.001), and did not significantly differ from the others in esthetics. Users preferred significant more the WA retainers in comparison with the CT retainers. The occlusal interference caused by the CT was positively correlated to other perceptions, such as changes in speech and discomfort. WA retainers presented similar preference and perceptions, but were significantly better than the CT. The CT occlusal coverage appeared to be the primary cause of its rejection.